THE EFFECT OF KNOWLEDGE SHARING, INNOVATIVE BEHAVIOR AND ENTREPRENEURIAL ORIENTATION ON THE PERFORMANCE OF CULINARY INDUSTRY - Chichi Andriani; Yunia Wardi; Susi Evanita (Jurnal Apresiasi Ekonomi, 2025)
This study aims to analyze the effect of knowledge sharing, innovative behavior and entrepreneurial orientation on the performance of culinary industry SMEs in Padang city. The population in this study were all culinary industry SMEs in Padang city with a target sample of culinary SMEs with a total of 155 samples. Data analysis techniques using multiple linear regression analysis. From the results obtained that 1) knowledge sharing has a significant influence on the performance of SMEs culinary industry in Padang city, 2) innovative behavior has a significant influence on the performance of SMEs culinary industry in Padang city and 3) entrepreneurial orientation does not have a significant influence on the performance of SMEs culinary industry in Padang city.